Britain's baker's dozen of disasters: The UK's thirteen worst economic policy mistakes since 1900 - Peter Clarke; Robert C. B. Miller (Institute of Economic Affairs (IEA), 2015)
Tribute bands are (or were) all the rage. And this is tribute book. Unashamedly we have stolen the idea of Britain's Baker's Dozen of Disasters from Burton A. Abrams's book, The Terrible 10: A Century of Economic Folly, which records the ten worst American economic policy follies in the last hundred years (Abrams 2013). Our book is about the thirteen worst economic policy decisions in British history since 1900, selected on the grounds of the ill consequences that flowed from them. We have chosen to describe 13 rather than 10 because of the sheer wealth of material. Indeed, we had difficulty in limiting the total to 13 as several other disasters have excellent qualifications for selection. Like Professor Abrams we have not sought to apportion blame amongst political parties or individuals, most of whom are long dead or at best political 'has-beens'. We have though sought to describe the particular beliefs, situations and temptations of those responsible. We have not attempted detailed descriptions but only reminders of the terrible, but well-intended, mistakes of the past. It was Enoch Powell who declared that countries can eventually become resistant to repeating the same economic mistakes. Thus he found it inconceivable that Germany should ever again depreciate its currency after the hyperinflations that followed both world wars. Similarly, he claimed that Britain would never repeat the catastrophe of an over-valued exchange rate that culminated in the humiliation of 1931. Mr Powell was over-optimistic as he made his comment before the Britain joined the Exchange Rate Mechanism - or 'Eternal Recession Mechanism' as it was christened by Norman Tebbit. Perhaps a mistake must be repeated before immunity is acquired. Britain has well-established form in making economic policy mistakes. In comparing the economic policy disasters of Britain and America, a number of differences stand out. Of course, some are the result of the UK and the US having large differences in population, political institutions, geography and patterns of trade. America, not being as dependent on foreign trade, never suffered Britain's exchange rate travails. But perhaps the greatest difference is that in the twentieth century Britain suffered from a strand of vehement socialism which ran from Sidney and Beatrice Webb and the Fabians until it was surgically removed by Tony Blair and 'New Labour', surely Mrs Thatcher's lasting monument.1 Fabian socialism had two major themes, which distorted and damaged the British economy for the greater part of the 20th century. First was a belief that nationalisation and municipalisation were the best ways of organising industry and commerce. Second was a belief in equality, which was to be enforced by high marginal rates of taxation on incomes, inheritances, gifts and capital gains. Economic policies based on these doctrines were destructive and kept millions of Britons (and others) in wholly preventable poverty. The consequences also affected Britain's standing in the world. While countries such as West Germany prospered in the 1950s, 1960s and 1970s, Britain lagged with slow growth, ever-quickening inflation and a declining reputation. Britain's economic weakness was even an important factor in deciding the outcome of the Suez imbroglio. The other major source of economic mayhem in the last hundred years has been British policymakers' obsession with the exchange rate. As we shall see, in the 1920s there may have been some justification for seeking to return to the international gold standard as it existed in the happy days before World War I. But determination to protect an arbitrary exchange rate of 2.8 to 1 in the 1950s and 1960s seems quixotic, while the attempt to link sterling to the Deutsche Mark in the ERM in the 1990s appears in retrospect to be merely bonkers. The inevitable debacle of 'White Wednesday' destroyed the Conservatives' reputation for economic competence for three parliaments. No attempt is made to gauge which of the disastrous 13 was the worst or to estimate how much damage each caused. Such calculations may be possible but we have not attempted them. Can one draw any general conclusions about the Disastrous 13? Firstly, many of the errors stem from the rejection of Victorian individualism - numbers 1, 2 and 4, respectively Trade Union Immunities, Edwardian Liberal Welfare Reforms and Abandoning Free Trade, stand out. Secondly, the feebleness of the Conservative government 1951-1964 is extraordinary. Particularly striking is the fact that successive Conservative chancellors did not reduce the very high marginal rates of personal taxation they inherited from Mr Attlee's government. Their failure even to attempt privatisation (other than iron and steel) or to learn from the successes of the liberal economics of the German soziale marktwirtshaft is telling. Are we sanguine that future governments will avoid repeating the mistakes of the past or making new ones? One fact inclines us to moderate optimism: the extraordinary transformation of China brought about by vigorous capitalism. Hundreds of millions have been removed from poverty in a few decades and there is no reason to think the process is close to an end. This example may prevent British politicians from a repetition of some of the worst errors of the past. Still, like Peter Cook's character, they may still be able to say: 'I have learned from my mistakes, and I am sure I can repeat them exactly'.
Keywords: 330; Economic policy; Criticism; History; Great Britain; Wirtschaftspolitik; Kritik; Geschichte; Großbritannien